An Analysis of Students’ Attitude in Using Social Media Learning English : A Blended Learning Approach - Karmila Sari, Rita; Auliya, Risma Nurul (IJET (Indonesian Journal of English Teaching), 2021)
This study aims to find out how students' attitudes in using social media in learning English with blended learning. This research is a survey research with quantitative approach. This research was conducted at a private university in East Jakarta. The research population included 87 Informatics Study Program students, consisting of 71 male and 16 female students. The research instrument was in the form of a questionnaire revealing about students' perceptions towards blended learning and the use of social media in learning English, which consisted of three parts, namely: student data (6 items); English learning model choices (7 items); and students' perceptions about the use of social media, including attitudes and problems encountered in learning English (15 items). The research data were analyzed using the one-way ANOVA test and t-test. The findings showed that the frequency of the use of the internet or electronic media for learning or obtaining information within 1 day affected the attitudes of students in the use of social media in English learning. However, the results of the study also showed there is no significant difference in students' attitudes in using social media in learning English based on their gender.